2016
DOI: 10.1098/rspa.2016.0095
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dopant substitution mechanism on catalytic properties within hierarchical architectures

Abstract: A range of hierarchically porous (HP) AlPO-5 catalysts, with isomorphously substituted transition metal ions, have been synthesized using an organosilane as a soft template. By employing a range of structural and spectroscopic characterization protocols, the properties of the dopant-substituted species within the HP architectures have been carefully evaluated. The resulting nature of the active site is shown to have a direct impact on the ensuing catalytic properties in the liquid-phase Beckmann rearrangement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 62 publications
(93 reference statements)
2
8
0
Order By: Relevance
“…n ‐Propylamine TPD was used to probe the Brønsted acidity and to quantify the density of the Brønsted acid sites. The desired density of the Brønsted acid sites was 0.1 mmol g −1 , a value that was previously reported for most of the materials synthesized in this work . Table shows that the density of acid sites varies somewhat between the +2 and +4 metals.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…n ‐Propylamine TPD was used to probe the Brønsted acidity and to quantify the density of the Brønsted acid sites. The desired density of the Brønsted acid sites was 0.1 mmol g −1 , a value that was previously reported for most of the materials synthesized in this work . Table shows that the density of acid sites varies somewhat between the +2 and +4 metals.…”
Section: Resultssupporting
confidence: 68%
“…The desired density of the Brønsted acids ites was 0.1 mmol g À1 ,a value that was previously reported form ost of the materials synthesized in this work. [37,43] Table 1s hows that the density of acid sites varies somewhat between the + 2a nd + 4m etals. The density of acid sites is lower for the + 4m etals than for the + 2m etals,r anging from 0.060 to 0.065 and 0.068 mmol g À1 forH -TiAlPO-5, H-ZrAlPO-5, and H-SAPO-5,r espectively.T his is in agreementw ith the + 4m etalsb eing less likely to substitute into the framework, asP ÀOb onds are more covalenti nc haracter than AlÀOb onds in the ALPO-5 framework.…”
Section: Synthesis and Catalyst Characterizationmentioning
confidence: 99%
“…These species offer alternative binding sites for the NPs, in the mesopores, preventing near-complete blockage of the micropores, as seen in PdAu/MP-SAPO-5 ( Table 1 ). Further, it is has previously been shown that the presence of larger mesopores, in hierarchical systems, aids mass-transport to the catalyst surface and pore-diffusion to and from the active site [ 38 , 39 ]. In doing so, this can improve catalytic activity compared to purely microporous species, which may also be a secondary factor.…”
Section: Resultsmentioning
confidence: 99%
“…The micelles and surface-directing agents were removed by calcination to create HP-AlPO framework with silanol lined mesopores. In our previous reports, we have successfully demonstrated the synthesis of HP framework by adding dimethyloctadecyl[(3-(trimethoxysilyl)propyl] ammonium chloride (DMOD) micellar agent, along with silica source during the AlPO synthesis, in which silanol lined mesopores were formed along with micropores to generate HP silicoaluminophosphate (SAPO) frameworks [ 38 , 39 , 40 , 41 ]. The amount of Si loading was fixed in order to avoid Si islanding within the framework, which lowers the overall number of active sites [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Newland et al [4] describe the influence of dopant substitution mechanism on catalytic properties within hierarchical architectures. They show how hierarchically porous AlPO-5 catalysts can be designed with isomorphously substituted transition metal ions and that the resulting active sites produced can influence the reactivity in the liquid-phase Beckmann rearrangement of cyclic ketones.…”
Section: Gjh 0000-0001-8885-1560mentioning
confidence: 99%